Management of captive young elephants in Kerala - Acty George (Department of Livestock Production Management, college of veterinary and animal sciences, 2006)
The present study was undertaken to suggest suitable recommendations in the management of captive young elephants of Kerala after assessing the existing management, feeding and training practices through survey method. The credibility of information collected was cross checked with physical verification.